2020
DOI: 10.1056/nejmoa2001316
|View full text |Cite
|
Sign up to set email alerts
|

Early Transmission Dynamics in Wuhan, China, of Novel Coronavirus–Infected Pneumonia

Abstract: We collected information on demographic characteristics, exposure history, and illness timelines of laboratory-confirmed cases of NCIP that had been reported by January 22, 2020. We described characteristics of the cases and estimated the key epidemiologic time-delay distributions. In the early period of exponential growth, we estimated the epidemic doubling time and the basic reproductive number. RESULTSAmong the first 425 patients with confirmed NCIP, the median age was 59 years and 56% were male. The majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

491
14,129
99
661

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14,963 publications
(15,888 citation statements)
references
References 15 publications
491
14,129
99
661
Order By: Relevance
“…On the basis of the initial investigation, the shared history of exposure to the Wuhan Seafood Wholesale Market highly suggested that wild animals sold in the market such as bamboo rats, raccoons, and snakes would be the original source of the novel virus. 16 Soon afterwards, the traceability analysis supported that the 2019-nCoV would be from Rhinolophus. This is with the phylogenetic analysis results that the 2019-nCoV was most related to BatCoV RaTG13 from the bat.…”
Section: Epidemiologymentioning
confidence: 88%
See 1 more Smart Citation
“…On the basis of the initial investigation, the shared history of exposure to the Wuhan Seafood Wholesale Market highly suggested that wild animals sold in the market such as bamboo rats, raccoons, and snakes would be the original source of the novel virus. 16 Soon afterwards, the traceability analysis supported that the 2019-nCoV would be from Rhinolophus. This is with the phylogenetic analysis results that the 2019-nCoV was most related to BatCoV RaTG13 from the bat.…”
Section: Epidemiologymentioning
confidence: 88%
“…10 , 18 , 19 Importantly, the people who are primary, asymptomatic and in incubation period are the main sources of infection, which is of critical significance to the epidemic prevention and control. 16 Up to now, respiratory droplets is the major route of transmission. Besides, the fecal-oral route of transmission is considered but unconfirmed because 2019-nCoV nucleic acids could be detected in the stool samples of pneumonia patients with abdominal symptoms.…”
Section: Epidemiologymentioning
confidence: 99%
“…SARS-CoV-2 seems to mostly be spread by droplets, and not through air. Nosocomial transmission have been described, 49 and superspreading events in hospital settings may occur. SARS-CoV-2 is possibly spreading indirectly through contaminated surfaces and hand contamination as well, but the lack of aerosol transmission will make the spread less efficient.…”
Section: Close-up Of the Sars-cov-2mentioning
confidence: 99%
“…The virus-specific nucleic acid sequences have been detected in lung fluid, throat, oropharyngeal and nasopharyngeal swab samples [3]. Due to lack of sufficient awareness of the COVID-19 in the early stages of the epidemic, some healthcare workers (HCWs) have been infected [4,5]. Patients with symptoms of VOVID-19 may present to Ear Nose and Throat ENT Departments.…”
Section: Abbreviationsmentioning
confidence: 99%
“…To decrease the density of patients, the ENT department separated the waiting area from the treatment area, reduced the number of appointments, scheduled appointments at different times, and increased online consulting services. In addition, taking account of the facts that the median age of COVID-19 patients was 59 years and that morbidity and mortality is greater in the elderly [4], HCWs older than 65 years of age were suspended from outpatient activities. Further, our escalation plan is that if the number of COVID-19 cases continues to rise, only emergency services will be maintained.…”
Section: Moreover Diagnostic and Therapeutic Procedures In Ent Departmentioning
confidence: 99%